Simultaneous Vector Bend and Temperature Sensing Based on a Polymer and Silica Optical Fibre Grating Pair - Binbin Yan; Guoqiang Liu; Jun He; Yanhua Luo; Liwei Yang; Haifeng Qi; Xinzhu Sang; Kuiru Wang; Chongxiu Yu; Jinhui Yuan; Gang-Ding Peng (Sensors, 2018)
The bending response of polymer optical fibre Bragg grating (POFBG) and silica optical fibre Bragg grating (SOFBG) mounted on a brass beam have been systematically studied and compared. The results indicate that POFBG has higher (almost twice as much) bend sensitivity than SOFBG. Based on the difference between the bend and temperature sensitivity of POFBG and SOFBG, a new method of measuring vector bend and temperature simultaneously was proposed by using a hybrid sensor head with series connection of one POFBG and one SOFBG with different Bragg wavelengths. It provides high sensitivity and resolution for sensing bend and temperature changes simultaneously and independently. The proposed sensor can find some applications in the fields where high sensitivity for both bend and temperature measurements are required.